(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Acid rain, a harmful environmental phenomenon, has become one of the most significant ecological problems in the modern world. It is mainly caused by the emission of sulfur dioxide (SO2) and nitrogen oxides (NOx) from industrial activities, such as fossil fuel combustion in power plants and automobiles. This research aims to explore the causes, effects, and reduction strategies for acid rain. It reviews the historical development of acid rain, its impact on ecosystems, human health, and infrastructure, and discusses various methods used worldwide to mitigate its effects. Through secondary data analysis, this study highlights the areas most affected by acid rain and provides recommendations for global efforts to reduce its occurrence and impact.